dATF4 regulation of mitochondrial folate-mediated one-carbon metabolism is neuroprotective - Celardo, Ivana (Cell Death Differ, 2017)
Neurons rely on mitochondria as their preferred source of energy. Mutations in PINK1 and PARKIN cause neuronal death in early-onset Parkinson's disease (PD), thought to be due to mitochondrial dysfunction. In Drosophila pink1 and parkin mutants, mitochondrial defects lead to the compensatory upregulation of the mitochondrial one-carbon cycle metabolism genes by an unknown mechanism. Here we uncover that this branch is triggered by the activating transcription factor 4 (ATF4). We show that ATF4 regulates the expression of one-carbon metabolism genes SHMT2 and NMDMC as a protective response to mitochondrial toxicity. Suppressing Shmt2 or Nmdmc caused motor impairment and mitochondrial defects in flies. Epistatic analyses showed that suppressing the upregulation of Shmt2 or Nmdmc deteriorates the phenotype of pink1 or parkin mutants. Conversely, the genetic enhancement of these one-carbon metabolism genes in pink1 or parkin mutants was neuroprotective. We conclude that mitochondrial dysfunction caused by mutations in the Pink1/Parkin pathway engages ATF4-dependent activation of one-carbon metabolism as a protective response. Our findings show a central contribution of ATF4 signalling to PD that may represent a new therapeutic strategy. A video abstract for this article is available at https://youtu.be/cFJJm2YZKKM.